The Correlation of Sentence Mastery and Learning Motivation with Service Letter Writing Skills - Saadah, Rahmawati; Hastuti, Hastuti; Sudarmaji, Sudarmaji (IJLHE: International Journal of Language, Humanities, and Education, 2019)
The skill of writing official letters in Indonesian language lessons is very important and closely related to other learning. In this study, the researchers investigate the skills of writing official letters with mastery of writing and learning motivation. Writing ability and learning motivation are independent variables, and official letter writing skills are dependent variables. In addition, this study uses quantitative research methods, where the results are in the form of numbers calculated using statistical calculations. From the study results, it was found that there was a very close relationship between writing mastery and learning motivation on the skills of writing official letters. The closeness of the relationship can be singly or jointly, where the skills of writing official letters for class VII students of MTs N 2 Bandar Lampung for the 2018/2019 academic year are improving.